HUBUNGAN ASUPAN VITAMIN B12, ASAM FOLAT, DAN ZINC DENGAN TINGKAT DEPRESI PADA PENYINTAS GANGGUAN BIPOLAR TIPE II DI KOMUNITAS BIPOLAR CARE INDONESIA - Syahya Padlatun Tayyibah (2020)
Bipolar Disorder is a type of psychiatric disorder that has several characteristics, there are depression episode, manic or hypomanic episode, and mixture episode. Bipolar Disorder Type II itself is indicated by hypomanic episode and depression episode. Indonesia claimed 2% for a high of Bipolar prevalence in 2017. This research intends to analyze the correlation of vitamin B12, folic acid, and zinc intake with depression level in Bipolar Disorder type II subjects at Bipolar Care Indonesia community. This research is observational by cross-sectional approach. The total of respondent in this research is 42 samples. The respondents are choosen by Consecutive Sampling technique. The data are taken by filling out the questionnaire Patient Health Questionnaire-9 (PHQ-9) and Semi Quantitative-Food Frequency Questionnaire (SQ-FFQ) through online interview. Chi-Square analysis outcome states that, there is correlation between vitamin B12 and folic acid intake with depression level (p value = 0,000 and 0,002). However, it is not found the correlation between zinc intake with depression level (p value = 0,530). It is reccomended to maintain the sanity by consuming the food intake that contain vitamin B12, folic acid, and zinc.